Factor affecting the customer intention to purchase online / Muhammad Syauqi Rozlee - Rozlee, Muhammad Syauqi (Faculty of Business and Management, 2018)
Nowadays, globalization without barriers which is the existance of internet that become one of the most effective communication channel had created opportunity for business to get bigger and reduce cost. Furthermore, In this era of globalization people tend to shop more through online platform. The purpose of this study were to examine the relationship between independent variables (perceived risk, perceived ease of use, perceieved usefulness, perceived enjoyment) and dependent variable (Customer intention to shop online) and to identify the most influence factor on customers’ intention to shop online. The sample size of this research is 150 respondents. Researcher use convenience sampling as the collection of the information is randomly picked up to anyone using questionnaires. Researcher using questionnaire as the method to collect all the data from the respondents in accomplishing the objectives.The outcome of respondents of multiple regression analysis showed that perceived ease of use, perceived usefulness, and perceived enjoyment have positive significant impact on customers; intention. However, perceived risk variable recorded insignificant relationship with customers’ intention to shop online. Beneficial to the future online retailer or existing online retailers in Malaysia in situation they want to cater customers to shop online. It will helps them to gain awareness and step to increase customers engagement. The discussion and recommendation for future research are also have been discussed in chapter.